Lack of placental neurosteroid alters cortical development and female somatosensory function - Bakalar, Dana; O’Reilly, Jiaqi J.; Lacaille, Helene; Salzbank, Jacquelyn; Ellegood, Jacob; Lerch, Jason P.; Sasaki, Toru; Imamura, Yuka; Hashimoto-Torii, Kazue; Vacher, Claire-Marie; Penn, Anna A. (Frontiers in Endocrinology, 2022)
Placental endocrine function is essential to fetal brain development. Placental hormones include neurosteroids such as allopregnanolone (ALLO), a regulator of neurodevelopmental processes via positive allosteric modulation of the GABAA receptor (GABAA-R). Using a mouse model (plKO) in which the gene encoding the ALLO synthetic enzyme is specifically deleted in trophoblasts, we previously showed that placental ALLO insufficiency alters cerebellar white matter development and leads to male-specific autistic-like behavior. We now demonstrate that the lack of placental ALLO causes female-predominant alterations of cortical development and function. Placental ALLO insufficiency disrupts cell proliferation in the S1 somatosensory cortex in a sex-linked manner. Early changes are seen in plKO embryos of both sexes, but persist primarily in female offspring after birth. Adolescent plKO females show significant reduction in pyramidal neuron density, as well as somatosensory behavioral deficits as compared with plKO males and control littermates. Assessment of layer-specific markers in human postmortem cortices suggests that preterm infants may also have female-biased abnormalities in cortical layer specification as compared with term infants. This study establishes a novel and fundamental link between placental function and sex-linked long-term neurological outcomes, emphasizing the importance of the growing field of neuroplacentology.